THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN INSTITUTIONAL EXCELLENCE - Nilufar Giyazova Shoir qizi (Bright Mind Publishing, 2025)
Transformational Leadership Theory offers a compelling framework for understanding how leaders in higher education institutions (HEIs) can inspire innovation, foster collaboration, and cultivate a sustainable culture of excellence. Unlike transactional approaches, transformational leadership emphasizes emotional engagement, shared vision, and personal development. This study explores how the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—can be applied to address the challenges of change management and quality enhancement in HEIs. Drawing on case studies from various national contexts and evaluating the reforming landscape in Uzbekistan, this paper argues that transformational leadership is vital for meaningful educational reform and institutional success.
Keywords: Transformational Leadership, Higher Education, Change Management, Institutional Reform, Academic Leadership, Motivation.